UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM MENGGUNAKAN MODEL-MODEL PEMBELAJARAN ACTIVE LEARNING MELALUI WORKSHOP DI SMKN 1 BANDAR SEIKIJANG PROVINSI RIAU - NASRIL NASRIL (LP2MTBM MAKARIOZ, 2022)
The problem in this study is that the teacher's ability to develop learning models has not been implemented as a whole, teachers use old learning models regardless of the characteristics of each student. teacher's ability to motivate children in learning is still low. The purpose of this study was to see the ability of teachers to use active learning models through workshops. This type of research is school action research. This research took place at SMKN 1 Bandar Seikijang, Riau Province. The subjects in this study were teachers at SMKN 1 Bandar Seikijang. The research procedure uses 4 stages, namely planning, implementation, observation and reflection. The data needed in this study were obtained through observation (observation). Data analysis was carried out by paying attention to the acquisition of the study instrument to see the ability of the teacher using a predetermined formula. Based on the results of the research and discussion that have been put forward in the previous chapter, it can be concluded that the workshop activities can improve the ability of teachers to use active learning models at SMKN 1 Bandar Seikijang, Riau Province. This is evidenced by an increase in the ability of teachers from cycle I to cycle II. The average percentage of the teacher's ability to use learning models in the first cycle was 63.1% in the sufficient category, in the second cycle it was 88.1% in the very good category.